Beyond Breast and Ovarian Cancers: PARP Inhibitors for BRCA Mutation-Associated and BRCA-Like Solid Tumors - O'Sullivan, Ciara C.; Moon, Dominic H.; Kohn, Elise; Lee, Jung-Min (Frontiers in Oncology, 2014)
Poly(ADP-ribose) polymerase inhibitors (PARPi) have shown clinical activity in patients with germline BRCA1/2 mutation (gBRCAm)-associated breast and ovarian cancers. Accumulating evidence suggests that PARPi may have a wider application in the treatment of cancers defective in DNA damage repair pathways, such as prostate, lung, endometrial, and pancreatic cancers. Several PARPi are currently in phase I/II clinical investigation, as single agents and/or in combination therapy in these solid tumors. Understanding more about the molecular abnormalities involved in BRCA-like phenotype in solid tumors beyond breast and ovarian cancers, exploring novel therapeutic trial strategies and drug combinations, and defining potential predictive biomarkers, are critical to expanding the field of PARPi therapy. This will improve clinical outcome in advanced solid tumors. Here we briefly review the preclinical data and clinical development of PARPi, and discuss its future of development in solid tumors beyond gBRCAm associated breast and ovarian cancers.